Typologies of social deviance in Serbian theoretical thought - Jugović Aleksandar (Sociologija, 2007)
The article analyzes the typologies of forms of social deviance created by Serbian theoreticians. The descriptive-critical method is applied in analyzing five important theoretical concepts and their underlying similarities and differences. The notion of social pathology itself is also discussed.